ANALISIS PENGUATAN AKIDAH ISLAM PADA GENERASI MUDA DI ERA GLOBALISASI - Cindy Olivia Natasya; Ninis Sekar Ayu; Nurul Afni; Muhammad Rifai Harahap (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to analyze the importance of strengthening Islamic faith (aqidah) among the younger generation in the era of globalization, which is characterized by the rapid advancement of information and communication technology. This research employs a literature review method by examining various sources, including academic journals, books, and relevant previous studies. The findings indicate that globalization presents significant challenges through the influx of values and cultures that are not always aligned with Islamic teachings, thereby potentially weakening the faith of the younger generation. Islamic moral and faith-based education plays a crucial role as a foundation for shaping students’ character, morality, and personality. Strengthening Islamic faith can be achieved through enhancing Islamic digital literacy, integrating religious values into educational practices, promoting the role of teachers as role models, and fostering support from families and the broader community. Therefore, adaptive and contextual Islamic education is essential to enable the younger generation to the challenges of globalization without losing their Islamic identity and values.